Versatility of GC-Orbitrap mass spectrometry for the ultra-trace detection of persistent organic pollutants in penguin blood from Antarctica - Warner, Nicholas; Cojocariu, Cristian; Scientific, ThermoFisher (2018)
Using GC Orbitrap mass spectrometry to address analytical challenges with trace level detection of persistent organic pollutants in Antarctica.
Keywords: Antarktis; biologi; miljøgifter; pingviner; zoologi

Carsten Borchgrevink and the Southern Cross Expedition, 1898-1900 - Riffenburgh, Beau; Kløver, Geir O (Red.) (The Fram Museum, 2017)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Commonness and rarity in the marine biosphere - Connolly, Sean R; MacNeil, M Aaron; Caley, M Julian; Knowlton, Nancy; Cripps, Ed; Hisano, Mizue; Thibaut, Loïc M; Bhattacharya, Bhaskar D; Benedetti-Cecchi, Lisandro; Brainard, Russell E; Brandt, Angelika; Bulleri, Fabio; et al. (Proceedings of the National Academy of Sciences, 2014)
Tests of biodiversity theory have been controversial partly because alternative formulations of the same theory seemingly yield different conclusions. This has been a particular challenge for neutral theory, which has dominated tests of biodiversity theory over the last decade. Neutral theory attributes differences in species abundances to chance variation in individuals’ fates, rather than differences in species traits. By identifying common features of different neutral models, we conduct a uniquely robust test of neutral theory across a global dataset of marine assemblages. Consistently, abundances vary more among species than neutral theory predicts, challenging the hypothesis that community dynamics are approximately neutral, and implicating species differences as a key driver of community structure in nature.Explaining patterns of commonness and rarity is fundamental for understanding and managing biodiversity. Consequently, a key test of biodiversity theory has been how well ecological models reproduce empirical distributions of species abundances. However, ecological models with very different assumptions can predict similar species abundance distributions, whereas models with similar assumptions may generate very different predictions. This complicates inferring processes driving community structure from model fits to data. Here, we use an approximation that captures common features of “neutral” biodiversity models—which assume ecological equivalence of species—to test whether neutrality is consistent with patterns of commonness and rarity in the marine biosphere. We do this by analyzing 1,185 species abundance distributions from 14 marine ecosystems ranging from intertidal habitats to abyssal depths, and from the tropics to polar regions. Neutrality performs substantially worse than a classical nonneutral alternative: empirical data consistently show greater heterogeneity of species abundances than expected under neutrality. Poor performance of neutral theory is driven by its consistent inability to capture the dominance of the communities’ most-abundant species. Previous tests showing poor performance of a neutral model for a particular system often have been followed by controversy about whether an alternative formulation of neutral theory could explain the data after all. However, our approach focuses on common features of neutral models, revealing discrepancies with a broad range of empirical abundance distributions. These findings highlight the need for biodiversity theory in which ecological differences among species, such as niche differences and demographic trade-offs, play a central role.
Keywords: Sørishavet; biodiversitet; biologi; marin økologi; marine økosystemer; polarområdene; zoologi

Fjerning av reinsdyr på Sør-Georgia: nok et avsluttet kapittel i norsk hvalfangsthistorie - Kilander, Carl Erik (Polarboken, 2014)
Keywords: Sørishavet; zoologi; økologi